2015
DOI: 10.1155/2015/243867
|View full text |Cite
|
Sign up to set email alerts
|

CHF Enhancement of Advanced 37-Element Fuel Bundles

Abstract: A standard 37-element fuel bundle (37S fuel bundle) has been used in commercial CANDU reactors for over 40 years as a reference fuel bundle. Most CHF of a 37S fuel bundle have occurred at the elements arranged in the inner pitch circle for high flows and at the elements arranged in the outer pitch circle for low flows. It should be noted that a 37S fuel bundle has a relatively small flow area and high flow resistance at the peripheral subchannels of its center element compared to the other subchannels. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This can also affect the enthalpy redistribution of the fuel bundle and finally enhance the CHF or dryout power. Both studies were found to be very effective at enhancing the CHF or dryout power through moving the first CHF location occurring at the center subchannels to the other subchannels of a 37S fuel bundle [6]. CHF experiments have been performed at Stern Laboratory to introduce a 37S fuel bundle with a small center element to the commercial reactors [4].…”
Section: Introductionmentioning
confidence: 99%
“…This can also affect the enthalpy redistribution of the fuel bundle and finally enhance the CHF or dryout power. Both studies were found to be very effective at enhancing the CHF or dryout power through moving the first CHF location occurring at the center subchannels to the other subchannels of a 37S fuel bundle [6]. CHF experiments have been performed at Stern Laboratory to introduce a 37S fuel bundle with a small center element to the commercial reactors [4].…”
Section: Introductionmentioning
confidence: 99%